Symposium 7: Frameworks for the Representation and Analysis of Networked Learning Activity - McAteer, Erica; Marsden, Sally (Proceedings of the International Conference on Networked Learning, 2004)
This symposium presentation demonstrates grounded theoretical frameworks for the representation and analysis of networked learning activities and outcomes within their educational context. These frameworks provide for systematic and rigorous analysis of learning behaviours in context from a range of disciplinary perspectives for enquiry. They also allow re-examination of study cases from new enquiry perspectives. Two examples of the frameworks in use are provided, the first concerns the role of gender in networked learning, the second seeks evidence for influences of learning activity for learning outcomes. This paper provides some theoretical background and presents the context frame which situates framework for the representation of interactive learning behaviours.